Nice to your heart: A pilot community-based intervention to improve heart health behaviours in urban residents. (April 2016) - Carter, Stephanie R; Walker, Alia; Abdul-Latif, Safiyah; Maurer, Laurie; Masunungure, Daniel; Tedaldi, Ellen; Patterson, Freda
Objective: Efforts to improve cardiovascular health among adult African American populations, particularly through organised physical activity, have met with limited success. This study pilot-tested a novel soul line dancing and nutrition education programme ( Nice to Your Heart ) that was designed and implemented as part of an academic community-based collaboration. Design: Eight, 2-hour sessions were delivered to 38 eligible and consenting participants. Each session included 60 minutes of soul line dancing and up to 30 minutes of nutrition education. Methods: The outcomes of programme attendance including days physically active and fruit and vegetable consumption in the last week, as well as blood pressure, were assessed. Results: In all, 58% of the sample ( N = 13) attended five or more sessions, with women and those not currently employed more likely to achieve high attendance. Improvements in days active in the last week ( t = −8.69, p < .01) and fruit consumption ( t = −0.03, p = .04) were observed. Conclusion: These data show that this culturally sensitive programme of soul line dancing and nutrition education was well received and had positive indications for improved cardiovascular health in a high-risk group. A fully controlled trial is warranted to determine programme effectiveness.